2019
DOI: 10.1084/jem.20190787
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated Notch and Wnt signaling activates early-stage myeloid regeneration pathways in leukemia

Abstract: Targeting commonly altered mechanisms in leukemia can provide additional treatment options. Here, we show that an inducible pathway of myeloid regeneration involving the remodeling of the multipotent progenitor (MPP) compartment downstream of hematopoietic stem cells (HSCs) is commonly hijacked in myeloid malignancies. We establish that differential regulation of Notch and Wnt signaling transiently triggers myeloid regeneration from HSCs in response to stress, and that constitutive low Notch and high Wnt activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 56 publications
4
26
0
Order By: Relevance
“…Transcriptional analyses revealed that Cebpa deficiency prevents chronic IL-1βdriven activation of myeloid differentiation, as well as metabolic and proteostatic gene programs important for differentiation. Despite the pre-existing molecular priming of MPP3 toward myeloid lineage differentiation (Cabezas-Wallscheid et al, 2014;Pietras et al, 2015), our data show chronic IL-1β further activates these pathways, consistent with the capacity of myeloid lineage progenitors to overproduce myeloid cells in response to 'emergency' cues (Herault et al, 2017;Kang et al, 2020;Manz and Boettcher, 2014).…”
Section: Strikingly Chronic Il-1β Exposure Triggered a Fitness Advansupporting
confidence: 71%
“…Transcriptional analyses revealed that Cebpa deficiency prevents chronic IL-1βdriven activation of myeloid differentiation, as well as metabolic and proteostatic gene programs important for differentiation. Despite the pre-existing molecular priming of MPP3 toward myeloid lineage differentiation (Cabezas-Wallscheid et al, 2014;Pietras et al, 2015), our data show chronic IL-1β further activates these pathways, consistent with the capacity of myeloid lineage progenitors to overproduce myeloid cells in response to 'emergency' cues (Herault et al, 2017;Kang et al, 2020;Manz and Boettcher, 2014).…”
Section: Strikingly Chronic Il-1β Exposure Triggered a Fitness Advansupporting
confidence: 71%
“…Myeloid leukemias are frequently characterized by cohesin mutations, particularly in STAG2 . Furthermore, activation of Wnt signaling is associated with transformation in AML ( Wang et al, 2010 ; Beghini et al, 2012 ; Kang et al, 2020 ) and AML patients were identified with mutations in AXIN1 and APC that lead to stabilization of β-catenin ( Erbilgin et al, 2012 ). CMK is a Down Syndrome-derived megakaryoblastic cell line that typifies myeloid leukemias that are particularly prone to cohesin mutation ( Yoshida et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, expressed transcripts encoding Wnt signaling pathway components did not cluster differently in cohesin-deficient clones compared with parental MCF10A cells, and cohesin mutation-based clustering remained dominant (Figure 6figure supplement 1B). We reasoned that stimulation of Wnt signaling in a more responsive cell type might be necessary to determine how stabilized catenin in cohesin-deficient cells affects transcription.Myeloid leukemias are frequently characterized by cohesin mutations, particularly in STAG2.Furthermore, activation of Wnt signaling is associated with transformation in AML[55][56][57]…”
mentioning
confidence: 99%
“…Furthermore, activation of Wnt signaling is associated with transformation in AML [53][54][55] and AML patients were identified with mutations in AXIN1 and APC that lead to stabilization of b-catenin [56]. CMK is a Down Syndrome-derived megakaryoblastic cell line that typifies myeloid leukemias that are particularly prone to cohesin mutation [57].…”
Section: Cohesin-deficient Leukemia Cells Are Hypersensitive To Wnt Smentioning
confidence: 99%
“…The identification of PI3K/AKT/mTOR inhibitors in the screen supports this notion.Wnt signals are important for stem cell maintenance and renewal in multiple mammalian tissues[52]. Canonical Wnt signaling is required for self-renewal of leukemia stem cells (LSCs)[55], and is reactivated in more differentiated granulocyte-macrophage progenitors (GMPs) when they give rise to LSCs[53]. Wnt signaling is an important regulator of hematopoietic stem cell (HSC) self-renewal as well[64].…”
mentioning
confidence: 99%